HUBUNGAN METAKOGNISI DAN PROBLEM SOLVING MATEMATIKA PADA SISWA SMP - Agatha Vinika Putri; Heru Astikasari Setya Murti (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
This study is motivated by the importance of metacognitive skills in supporting junior high school students’ mathematical problem-solving abilities, particularly during early adolescence, a developmental stage characterized by rapid cognitive growth. The aim of this study is to examine the relationship between metacognitive skills and problem-solving abilities among junior high school students. This research employs a quantitative method with a correlational approach, involving 57 junior high school students aged 12–15 years. Data were collected using metacognitive skills and problem-solving scales that had been tested for validity and reliability, and were analyzed using descriptive statistics and Spearman’s correlation test due to non-normally distributed data. The results indicate a very strong and significant positive relationship between metacognitive skills and students’ problem-solving abilities, with a correlation coefficient of r = 0.894 and a significance value of p < 0.01. Descriptive analysis further reveals that the majority of students fall into the moderate category for both metacognitive skills and problem-solving abilities. These findings suggest that metacognitive skills play a crucial role in helping students understand problems, plan strategies, and evaluate the problem-solving process. The implications of this study highlight the importance of integrating metacognitive skill development into junior high school learning processes to enhance students’ problem-solving abilities optimally. ABSTRAK Penelitian ini dilatarbelakangi oleh pentingnya keterampilan metakognitif dalam mendukung kemampuan problem solving matematika siswa SMP, terutama pada fase remaja awal yang ditandai dengan perkembangan kemampuan berpikir yang pesat. Penelitian ini bertujuan untuk mengetahui hubungan antara keterampilan metakognitif dan kemampuan problem solving pada siswa SMP. Metode penelitian yang digunakan adalah penelitian kuantitatif dengan pendekatan korelasional. Subjek penelitian berjumlah 57 siswa SMP dengan rentang usia 12–15 tahun. Pengumpulan data dilakukan menggunakan skala keterampilan metakognitif dan skala problem solving yang telah diuji validitas dan reliabilitasnya. Analisis data dilakukan menggunakan statistik deskriptif dan uji korelasi Spearman karena data tidak berdistribusi normal. Hasil penelitian menunjukkan bahwa terdapat hubungan positif yang sangat kuat dan signifikan antara keterampilan metakognitif dan kemampuan problem solving siswa, dengan koefisien korelasi sebesar r = 0,894 dan nilai signifikansi p < 0,01. Hasil analisis deskriptif juga menunjukkan bahwa sebagian besar siswa berada pada kategori sedang baik dalam keterampilan metakognitif maupun kemampuan problem solving. Temuan ini mengindikasikan bahwa keterampilan metakognitif berperan penting dalam membantu siswa memahami masalah, merencanakan strategi, serta mengevaluasi proses penyelesaian masalah. Implikasi dari penelitian ini menunjukkan bahwa pengembangan keterampilan metakognitif perlu menjadi perhatian dalam proses pembelajaran di SMP guna meningkatkan kemampuan problem solving siswa secara optimal.